Academic writing for university students - Bailey, Stephen, 1947- (Routledge, Taylor & Francis Group, 2022)
"Academic Writing for University Students is designed to help all students succeed in writing essays, reports and other papers for coursework and exams effectively. Academic writing is often the biggest challenge facing college and university students, but this book provides all the tools needed to master the necessary skills. The book is divided into four parts, to help teachers and students easily find the help they need, both in the classroom and for self-study: The Writing Process: From finding suitable sources, through to editing and proofreading, Writing Types: Practice with common assignments such as reports and cause-effect essays, Writing Tools: Skills such as making comparisons, definitions, punctuation and style, Lexis: Academic vocabulary, using synonyms, nouns, adjectives, verbs and adverbs This key handbook breaks down and practises every stage of essay writing. All units are fully cross-referenced, and a complete set of answers to the practice exercises is included. In addition, the companion website hosts comprehensive teaching notes as well as more challenging exercises, revision material and links to other sources. Designed for self-study as well as classroom use, this book uses authentic academic texts from a range of sources and provides models for common writing tasks such as case studies, while progress checks are included for each part to enable students to assess their learning. Academic Writing for University Students is an invaluable guide to all aspects of academic writing in English"- Resumé vydavatel
Terminologický slovník
Keywords: angličtina; odborné písemné práce; odborné texty; odborný styl; odborný jazyk; vysoké školy; vysokoškolské studium; English language; professional papers; professional texts; professional style; professional language; universities and colleges; college study; akademické psaní; příručky; handbooks and manuals